2019
DOI: 10.1002/ptr.6504
|View full text |Cite
|
Sign up to set email alerts
|

Palmatine: A review of pharmacological properties and pharmacokinetics

Abstract: The aim of this review is to collect together the results of the numerous studies over the last two decades on the pharmacological properties of palmatine published in scientific databases like Scopus and PubMed, which are scattered across different publications. Palmatine, an isoquinoline alkaloid from the class of protoberberines, is a yellow compound present in the extracts from different representatives of Berberidaceae, Papaveraceae, Ranunculaceae, and Menispermaceae. It has been extensively used in tradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 127 publications
(144 reference statements)
0
38
0
Order By: Relevance
“…Of the 14 components, some have been shown to have anti-atherosclerosis effects in previous studies.With the most targets, it can be found from the literature that the research on the anti-atherosclerosis effect of quercetin is also the most extensive.Quercetin can improves blood vessel structure by reducing serum lipids, oxidative stress factors, aortic contraction, weight gain and blood pressure, prevents the formation of arterial plaques through antioxidant activity [25] ,and fight atherosclerosis by enhancing autophagy in ApoE-/-mice [26] .Furthermore, in a high fructose-induced atherosclerosis mouse model, quercetin can attenuate atherosclerosis by inhibiting inflammation and apoptosis through the PI3K / AKT signaling pathway regulated by reactive oxygen species [27] .Both beta-sitosterol and stigmasterol belong to Phytosterols, and moderate intake of Phytosterols is considered to reduce plasma cholesterol and prevent atherosclerosis [28] .In addition, Lifsey HC et al reported that stigmasterol can promote the excretion of cholesterol in the small intestine [29] , while Chien MH et al reported that beta-sitosterol can inhibit the proliferation of vascular smooth muscle cells and has a potential role in anti-atherosclerosis [30] .In the rabbit model of atherosclerosis induced by high cholesterol, kaempferol can regulate the expression of inflammatory factors, showing an anti-atherosclerosis effect [31] .Ku SK et al reported that wogonin and baicalein blocked hyperglycaemic vascular inflammation by inhibiting NF-κB in human primary endothelial cell models, suggesting that they had a therapeutic effect on atherosclerosis [32] .Shi Y et al reported that berberine can delay the progression of atherosclerosis in ApoE-/-mice induced by high-fat diet and reduce the expression of inflammatory factors, which may be related to the regulated intestinal flora [33] .Other studies have shown that berberine down-regulates visfatin expression to inhibit endothelial dysfunction and improve diet-induced atherosclerosis in ApoE-/-mice [34] .Feng M et al reported that in the atherosclerosis model of ApoE-/-mice, the intervention of coptisine can reduce the level of blood lipid and down-regulate the expression of relevant inflammatory cytokines, thus reducing the area of atherosclerotic plaque [35] .Although no previous studies have directly shown that palmatine, berberrubine, acetacetin, oroxylin a paly a role of anti-atherosclerosis, studies have shown that they all have different degrees of effects of anti-inflammatory, lipid-lowering, and anti-oxidation,et alBerberrubine is the main metabolite of berberine in vivo. Studies have shown that it can reduce blood lipid ,inhibit the activity of intracellular xanthine oxidase, and has a potential role in treating endothelial dysfunction [36][37] .Palmatine and oroxylin a both have anti-inflammatory effects,and the former can reduce blood lipid levels, while the latter can also inhibit intracellular lipid accumulation [38][...…”
Section: Figure7hljdd-key Active Ingredients-key Targets-pathway Netmentioning
confidence: 99%
“…Of the 14 components, some have been shown to have anti-atherosclerosis effects in previous studies.With the most targets, it can be found from the literature that the research on the anti-atherosclerosis effect of quercetin is also the most extensive.Quercetin can improves blood vessel structure by reducing serum lipids, oxidative stress factors, aortic contraction, weight gain and blood pressure, prevents the formation of arterial plaques through antioxidant activity [25] ,and fight atherosclerosis by enhancing autophagy in ApoE-/-mice [26] .Furthermore, in a high fructose-induced atherosclerosis mouse model, quercetin can attenuate atherosclerosis by inhibiting inflammation and apoptosis through the PI3K / AKT signaling pathway regulated by reactive oxygen species [27] .Both beta-sitosterol and stigmasterol belong to Phytosterols, and moderate intake of Phytosterols is considered to reduce plasma cholesterol and prevent atherosclerosis [28] .In addition, Lifsey HC et al reported that stigmasterol can promote the excretion of cholesterol in the small intestine [29] , while Chien MH et al reported that beta-sitosterol can inhibit the proliferation of vascular smooth muscle cells and has a potential role in anti-atherosclerosis [30] .In the rabbit model of atherosclerosis induced by high cholesterol, kaempferol can regulate the expression of inflammatory factors, showing an anti-atherosclerosis effect [31] .Ku SK et al reported that wogonin and baicalein blocked hyperglycaemic vascular inflammation by inhibiting NF-κB in human primary endothelial cell models, suggesting that they had a therapeutic effect on atherosclerosis [32] .Shi Y et al reported that berberine can delay the progression of atherosclerosis in ApoE-/-mice induced by high-fat diet and reduce the expression of inflammatory factors, which may be related to the regulated intestinal flora [33] .Other studies have shown that berberine down-regulates visfatin expression to inhibit endothelial dysfunction and improve diet-induced atherosclerosis in ApoE-/-mice [34] .Feng M et al reported that in the atherosclerosis model of ApoE-/-mice, the intervention of coptisine can reduce the level of blood lipid and down-regulate the expression of relevant inflammatory cytokines, thus reducing the area of atherosclerotic plaque [35] .Although no previous studies have directly shown that palmatine, berberrubine, acetacetin, oroxylin a paly a role of anti-atherosclerosis, studies have shown that they all have different degrees of effects of anti-inflammatory, lipid-lowering, and anti-oxidation,et alBerberrubine is the main metabolite of berberine in vivo. Studies have shown that it can reduce blood lipid ,inhibit the activity of intracellular xanthine oxidase, and has a potential role in treating endothelial dysfunction [36][37] .Palmatine and oroxylin a both have anti-inflammatory effects,and the former can reduce blood lipid levels, while the latter can also inhibit intracellular lipid accumulation [38][...…”
Section: Figure7hljdd-key Active Ingredients-key Targets-pathway Netmentioning
confidence: 99%
“…Our group has been committed to exploring antibacterial agents with unique structure skeletons and novel mechanisms, and extensive efforts have been made on structural modifications and antibacterial activity explorations of protoberberine alkaloid [7][8][9][10]. Palmatine (PMT, Figure 1), a representative protoberberine alkaloid extracted from the traditional Chinese medicine Coptis chinensis, possesses a special quaternary ammonium in its structure and has diverse pharmacological and biological activities, including anti-inflammatory, anti-cancer, antiviral, and neuro-protection [11][12][13]. Meanwhile, PMT and its derivatives showed a potential as antibacterial candidates with their antibacterial efficacy against both gram-positive and gram-negative bacteria (including Staphylococcus aureus, Escherichia coli, and so on), which has been disclosed by different groups [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…possesses a special quaternary ammonium in its structure and has diverse pharmacological and biological activities, including anti-inflammatory, anti-cancer, antiviral, and neuro-protection [11][12][13]. Meanwhile, PMT and its derivatives showed a potential as antibacterial candidates with their antibacterial efficacy against both gram-positive and gram-negative bacteria (including Staphylococcus aureus, Escherichia coli, and so on), which has been disclosed by different groups [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Palmatine, an isoquinoline alkaloid isolated from Fibraurea recisa Pierre (Chinese name: Huangteng), has a wide range of pharmacological and biological activities, such as antibacterial, antifungal, and antiviral effects. 10,11 Clinically, palmatine has been used for the treatment of surgical infections, respira-tory and urinary tract infections, conjunctivitis, and gynecological inflammation. 12 Due to the wide range of applications and exact efficacy in clinic, the demand for palmatine in the pharmaceutical market is growing.…”
Section: Introductionmentioning
confidence: 99%